2015
DOI: 10.1007/s10266-015-0196-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hangeshashinto on calprotectin expression in human oral epithelial cells

Abstract: Oral epithelial cells produce antimicrobial peptides (AMPs) to prevent microbial infection. Calprotectin (S100A8/S100A9) is one of these AMPs in oral epithelial cells, the expression of which is up-regulated by interleukin-1α (IL-1α). Hangeshashinto (HST) is a traditional Japanese herbal medicine that has anti-inflammatory effects. The purpose of this study was to investigate the effect of HST on the expression of calprotectin through the regulation of IL-1α in oral epithelial cells. Human oral epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…23 On the other hand, antibacterial peptide production involves 3,4-dihydroxybenzaldehyde, baicalin, and ginsenoside Rb1, which act on oral mucosal epithelial cells and are considered to protect them against bacterial infection by enhancing the production of the antimicrobial peptide calprotectin. 35 The present results revealed markedly lower numbers of bacteria in the TJ-14 group, suggesting antibacterial activity in the mucosa of anticancer drug-induced stomatitis. No significant differences were observed in body weight changes or food intake on Days 9 and 11 between the three groups.…”
Section: Discussionsupporting
confidence: 52%
“…23 On the other hand, antibacterial peptide production involves 3,4-dihydroxybenzaldehyde, baicalin, and ginsenoside Rb1, which act on oral mucosal epithelial cells and are considered to protect them against bacterial infection by enhancing the production of the antimicrobial peptide calprotectin. 35 The present results revealed markedly lower numbers of bacteria in the TJ-14 group, suggesting antibacterial activity in the mucosa of anticancer drug-induced stomatitis. No significant differences were observed in body weight changes or food intake on Days 9 and 11 between the three groups.…”
Section: Discussionsupporting
confidence: 52%
“…HST thus constitutes a promising therapy, the efficacy of which has been demonstrated via a clinical study with a high evidence level 22,44 . Basic research findings have indicated that HST enhances OUM healing through multiple pharmacological actions (e.g., anti-oxidant, anti-inflammatory, anti-bacterial, and analgesic activities) [23][24][25] . With regard to anti-inflammatory effects, we have shown that various ingredients in HST decrease the interleukin 1β-induced prostaglandin E2 (PGE2) production www.nature.com/scientificreports www.nature.com/scientificreports/ in HOKs with multi-targeting effects, such as dual suppression of cyclooxygenase-2 expression and PGE2 metabolic activity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, double-blind, placebo-controlled, randomized studies have reported that repetitive mouth-washing with HST was effective for the improvement of chemotherapy-induced OUM in patients with colorectal or gastric cancer 22 . Several in vitro studies also reported that HST induced antibacterial and antioxidant effects, suggesting that these effects were involved in the mechanisms of HST with respect to the improvement of OUM [23][24][25] . Moreover, our previous studies in vitro and in vivo revealed additional mechanisms of HST in OUM, including both anti-inflammatory and analgesic effects [26][27][28] .…”
mentioning
confidence: 92%
“…However, the level of increase in Z induced by NYT or citrus unshiu peel [NYT (% of control): 433.3 ± 19.5, citrus unshiu peel: 207.4 ± 28.0] was considerably smaller than that caused by OXA (% of control: 9,781.5 ± 252.9). Theoretically, kampo medicine comprises several medical herbal crude drugs; thus, it is considered to exert multiple actions (11,(44)(45)(46)(47)(48)(49)(50)(51). Furthermore, each action of kampo medicine is considered milder than that of a drug composed of only one component, such as western drugs.…”
Section: Discussionmentioning
confidence: 99%